Da frátria à devoração mútua: narrativas da nacionalidade no cinema brasileiro contemporâneo - de Oliveira, Marinyze Prates (Diálogos Latinoamericanos, 2012)
This article analyzes the images of nationality constructed by the Brazilian contemporary cinema, focusing on some works of two directors that elect Brazil as the focus of their productions: Walter Salles Júnior (Terra estrangeira, Central do Brasil, Abril despedaçado, Linha de passe) and Sérgio Bianchi (Cronicamente inviável, Quanto vale ou é por quilo?). Through quite peculiar ways of seeing the nation, both directors take part of a tradition which had on Cinema Novo one of their exponential moments, incessantly trying to understand what Brazil and Brazilians are about.